(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Alikulov B, Gulboev D, Maxammadieva D, Tillaeva Z, Olimjonova S, Ismailov Z. 2023. Isolation and characterization of endophytic bacteria from some halophytes in saline desert regions of Uzbekistan. Biodiversitas 24: 1279-1288. The present study described the experimental results of isolating, characterizing, and selecting promising endophytic bacteria strains from halophytic plants, such as Haloxylon aphyllum, Halocnemum strobilaceum, and Halostachys belangeriana. These common bacteria in the southwestern regions of Uzbekistan are recommended for practical applications. In the present experiments, the effect of treatment with 65 isolates of endophytic bacteria isolated from these plants on the germination of seeds of agricultural crops such as wheat, cotton, and cucumber was evaluated. The result shows 15 promising strains of endophytic-bacteria from halophytic plants were selected and identified using molecular genetic methods. Furthermore, for the first time, we researched the isolation of endophytic bacteria from H. aphyllum, H. strobilaceum, and H. belangeriana plants and studied their properties. The results are useful for efficiently cultivating agricultural crops in areas affected by stress factors.